Analisis Rasio Likuiditas Dan Aktivitas Pada Koperasi Pegawai Negeri ( KPN ) Dharma Bakti Guru-Guru Sekolah Dasar Kecamatan Tenggarong - Akhmad Sofyan Hamid (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2022)
The hypothesis that the writer stated in the this research as follows; the activity ratio in Koperasi Pegawai Negeri (KPN) Dharma Bakti disposed to experience the increasing for 2006 compare with 2005. For analysis requirements, discussion and financial ratio accounting, so it is being used cooperation financial data such as balance and loss profit acount. So that, from its source it can be known the development of financial ratio which is resulted from Koperasi Pegawai Negeri (KPN) Dharma Bakti.Key Word : cooperation